Flavor and product messaging are the two most important drivers of electronic cigarette selection in a choice-based task - Allison N. Baker (Nature Portfolio, 2021)
Abstract Electronic cigarette use—vaping—is increasingly popular. Various product factors may influence an individual’s choice of e-cigarette. To provide an evidence base for e-cigarette regulation, a better understanding of the role different product attributes play in product preferences is needed. Here, we used conjoint analysis to quantify different factors that influence e-cigarettes choices, including flavors, nicotine level, customizability, or use of e-cigarettes to manage appetite/food craving. Young adults completed a set of choice-based conjoint tasks online. Choice Based Conjoint analysis (CBC) was used to determine utility scores for each attribute. Young adults (n = 587) who vaped at least once per week were included in analyses; gender differences were explored. Flavor was the most important attribute (48.1%), followed by product messaging (21.0%) and nicotine level (15.3%). Within flavor, confectionery and fruit flavors had the highest utility scores, while classic menthol and tobacco flavors had the lowest. Men and women differed in flavors, nicotine levels, and product messaging that appealed most. Among young adults who vape weekly, flavor is the most important factor in e-cigarette preferences. Gender also factors into e-cigarette preferences, especially for preferred nicotine level. Understanding why individuals choose particular e-cigarette products will help inform public health efforts and policy making.